Recognising cultural capital through shared meaning-making in cross-cultural partnership practices - Zhang, Meng; Matthews , Kelly; Liu, Shuang (International Journal for Students as Partners, 2022)
There are growing scholarly conversations about involving culturally and linguistically diverse students in learner-teacher partnership practices—practices that can pave pathways toward greater inclusion in higher education. Theorising power and identity through the lens of culture invites recognition of differing ways of knowing, being, and doing that shape learner-teacher interactions in higher education. In this conceptual article, we offer a framework to further efforts of redistributing power through intercultural partnership praxis. Two vignettes drawing on lived experience of being in a cross-cultural learner-teacher partnership project are employed to reveal the theory-practice possibilities. We argue that the careful, critical attention on the role culture plays in the relational work of learner-teacher partnership advances more culturally responsive pedagogical collaborations in higher education. In doing so, partnership praxis moves closer toward recognition of cultural capital and redistribution of power for learners and teachers engaging in cross-cultural pedagogical partnership.